Aspiring to succeed: A model of entrepreneurship and fear of failure - Morgan, John; Sisak, Dana (Journal of Business Venturing, 2016)
Fear of failure can dominate the choices of individuals. We model its role in the decision to become an entrepreneur and subsequent investments made in pursuit of success using the framework of loss aversion. We show that when an individual's threshold for success is sufficiently high, fear of failure motivates additional investment. When the threshold for success is equal to the foregone outside option, on the other hand, fear of failure is always de-motivating. Finally, regardless of the success threshold, fear of failure is negatively associated with entry into entrepreneurship. Our findings highlight the importance of the interaction between the degree of fear of failure and the aspirations of the would-be entrepreneur.